Artificial Targets: a versatile cell-free platform to characterize CAR T cell function in vitro - Wang, Xueting; Tokarew, Nicholas J. A.; Borgelt, Nadine; Siemer, Ramona; Melo, Cristiane Casonato; Langer, Christian; Kasampalidis, Ioannis; Ogusuku, Isabella E. Y.; Cathomen, Toni; Gessner, Isabel; Dose, Christian; Fauerbach, Jonathan A.; et al. (Frontiers in Immunology, 2024)
Cancer immunotherapies using chimeric antigen receptor (CAR) T cells have tremendous potential and proven clinical efficacy against a number of malignancies. Research and development are emerging to deepen the knowledge of CAR T cell efficacy and extend the therapeutic potential of this novel therapy. To this end, functional characterization of CAR T cells plays a central role in consecutive phases across fundamental research and therapeutic development, with increasing needs for standardization. The functional characterization of CAR T cells is typically achieved by assessing critical effector functions, following co-culture with cell lines expressing the target antigen. However, the use of target cell lines poses several limitations, including alterations in cell fitness, metabolic state or genetic drift due to handling and culturing of the cells, which would increase variabilities and could lead to inconsistent results. Moreover, the use of target cell lines can be work and time intensive, and introduce significant background due to the allogeneic responses of T cells. To overcome these limitations, we developed a synthetic bead-based platform ("Artificial Targets") to characterize CAR T cell function in vitro. These synthetic microparticles could specifically induce CAR T cell activation, as measured by CD69 and CD137 (4-1BB) upregulation. In addition, engagement with Artificial Targets resulted in induction of multiple effector functions of CAR T cells mimicking the response triggered by target cell lines Formatted: Superscript including cytotoxic activity, as assessed by exposure of CD107a (LAMP-1), expression and secretion of cytokines, as well as cell proliferation. Importantly, in contrast to target cells, stimulation with Artificial Targets showed limited unspecific CAR T cell proliferation. Finally, Artificial Targets demonstrated flexibility to engage multiple co-stimulatory molecules that can synergistically enhance the CAR T cell function and represented a powerful tool for modulating CAR T cell responses. Collectively, our results show that Artificial Targets can specifically activate CAR T cells for essential effector functions that could significantly advance standardization of functional assessment of CAR T cells, from early development to clinical applications.